1981
DOI: 10.1038/icb.1981.29
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Murray Valley Encephalitis Virus and Other Arboviruses in the Ord River Valley 1972–1976

Abstract: Summary This paper summarizes the isolation of arboviruses from mosquitoes collected in the Ord Valley between 1972 and 1976. A total of one hundred and ninety five strains of at least fifteen antigenically distinct viruses have been isolated. Seven of these isolates appear to be ‘new’ antigenic types, and several are undergoing further testing. These are three new rhabdoviruses (Kununurra [OR194], a virus provisionally named Kimberley [OR250] and OR189 [provisionally named Parry's Creek]), three ungrouped, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

1981
1981
2002
2002

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 13 publications
2
33
0
Order By: Relevance
“…Serological studies (Stanley and Choo, 1961; showed wide-Spread prevalence of neutralizing antibodies among residents throughout the Kimberley, and studies in the Ord Valley have defined a recurrent annual pattern of MVE transmission (Liehne et al. 1976a;Liehne et al, 1981). The isolation of a further four strains of MVE from Derby in this study augments this data and adds to the evidence for MVE being endemic throughout the Kimberley region.…”
Section: (B) Virus Isolationsupporting
confidence: 68%
See 4 more Smart Citations
“…Serological studies (Stanley and Choo, 1961; showed wide-Spread prevalence of neutralizing antibodies among residents throughout the Kimberley, and studies in the Ord Valley have defined a recurrent annual pattern of MVE transmission (Liehne et al. 1976a;Liehne et al, 1981). The isolation of a further four strains of MVE from Derby in this study augments this data and adds to the evidence for MVE being endemic throughout the Kimberley region.…”
Section: (B) Virus Isolationsupporting
confidence: 68%
“…The predominance of viruses of the Koongol group among the isolates (7 of 13) is very similar to results from the Ord (Liehne et al, 1981). These Koongol group viruses consisted of two strains of Wongal and five nonhaemagglutinaling strains which have yet to be fully characterized (Liehne et al, 1981).…”
Section: (B) Virus Isolationsupporting
confidence: 64%
See 3 more Smart Citations